On meromorphic solutions of the systems of linear differential equations with meromorphic coefficients - Mokhonko, A. Z.; Mokhonko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.925.7 For systems of linear differential equations whose dimension can be decreased, we establish estimates for the growth of meromorphic vector solutions. As an essentially new feature, we can mention the fact that no additional restrictions are imposed on the order of growth of coefficients of the system.